Does It Pay to Treat Patients With Coronavirus Disease 2019? Social Perception of Physicians Treating Patients With Coronavirus Disease 2019 - Hareli, Shlomo; David, Or; Basis, Fuad; Hess, Ursula (Frontiers in Psychology, 2022)
During the coronavirus disease 2019 (COVID-19) pandemic, the public has often expressed great appreciation toward medical personnel who were often shown in the media expressing strong emotions about the situation. To examine whether the perception of people on a physician is in fact influenced by whether the physician treats patients with COVID-19 and the emotions they expressed in response to the situation, 454 participants were recruited in May 2020. Participants saw facial expressions of anger, sadness, happiness, and neutrality which supposedly were shown by physicians who were presented as working either in COVID-19 wards or in an internal medicine ward. Participants rated how competent, empathetic, caring, and likable each physician was, to what degree they would wish to be treated by each physician, and what salary each physician deserved. Physicians treating patients with COVID-19 were seen more positively and as deserving higher pay; they appeared more competent, caring, likable, and were more likely to be chosen as a caregiver compared to physicians not treating patients with COVID-19. The expressed emotions of physicians had a strong impact on how they were perceived, yet this effect was largely unrelated to whether they treated patients with COVID-19 or not such that happy physicians seemed more empathetic, caring, and likable than the physicians who showed negative emotions. Positive regard toward physicians treating patients with COVID-19 was associated with the fact that they were seen as saving lives and not due to the risk imposed by their work.